Quantum holographic criminology: paradigm shift in criminology, law, and transformative justice - Milovanovic, Dragan (Carolina Academic Press, 2014)
Introduction -- Classical-materialist paradigm v. process-informational paradigm -- Holographic principle, primacy of information, and assemblages -- The question of agency: quantum holography and schema qd -- Quantum holography at work: applications in criminology and law -- Transformative justice -- Conclusion -- References